Mulheres quilombolas do Brejo dos Crioulos: protagonismo no norte de Minas Gerais - Fagundes, Márcia Verssiane Gusmão (2023)
This thesis aims to analyze the participation of quilombola women from Brejo dos Crioulos as key people in the maintenance of territorialities and in the preservation of the territory. Thus, based on field work, with ethnographic foundations, semi-structured interviews were conducted with nine women from different communities belonging to Quilombo Brejo dos Crioulos, located in the north of the State of Minas Gerais. Quilombolas, mediated by their relations with the territory, contribute to the maintenance and preservation of territorialities. This work focuses on the daily experiences of quilombola women who by transmitting their knowledge, strengthen ties between people and consolidate territorialities. As a result, it was noticed that the actions carried out by quilombola women, understood as territorialities, broaden and reinforce identity processes in the communities. The quilombola women considered as 'references', are characterized by the positions, actions and activities they carry out in the communities, seeking the common good, such as midwives, party organizers, batuqueiras, presidents of the greengrocers or farmers, artisans, sweet bakers, teachers, among other community, religious, cultural and educational leaders. Thus, they all stay in the territory, increasingly aware that the fight cannot stop. The participation of the quilombola women in the process of struggle and reconquest of the territory resulted in the self-identification of the social group as a traditional community and the political and identity activities were expanded with devices that focus on daily experiences, ways of life, popular practices and knowledge, endorsed by its performance in the different areas of its territory. It was verified that in addition to daily obligations, quilombola women are mediators of memory, ancestry, identity, orality, culture, and religiosity. They are at the forefront of the relationships that are established between communities, family groups and collectivities in the territory. Observing the internal and external movements of quilombola women in the quilombola territory allowed us to understand, from their perspective, the center of life and the relationships that guarantee, materially and immaterially, the permanence of the group, through the use of land and their everyday experiences. Finally, it is understood that the fact that the quilombola women were subjects of the research had a positive impact on their social esteem, since they were singled out and recognized by members of the community. The data collected demonstrated that the individual and collective trajectories of quilombola women, in different contexts, collaborate for those of the territorialities. It is expected that the voices of the quilombola women are fully heard and their decisions are respected, since the communities exist and resist thanks to all the daily work carried out by them.